Study of The Influence of Sodium Hydroxide Addition in The Borohydride Dyeing Process - MEKSI, N.; KARELLE, S.; KECHIDA, M.; MHENNI, M.F. (Asian Journal of Chemistry, 2010)
In this paper, the reduction of indigo by sodium borohydride and the use of the reduced dye solution in the dyeing of cotton fabric were studied. The evaluation of the performance of the reduction reaction was carried out by the establishment of potentiometric titration procedure of the leuco-indigo concentration in the dyeing bath. The dyeing results were evaluated by measuring the colour yield (K/S) of the coloured samples at 660 nm. The influence of the amount of indigo and the addition of alkali on reduction performances and on the dyeing quality were discussed. In these studies, it appears that the maximum of the reduction yield and of the colour yield took place at 132.35 % of indigo. The addition of alkali slowed the rate of the reduction reaction of indigo by sodium borohydride. However, it enhanced the indigo reduction yield, the colour yield and notably sodium borohydride hydrolysis. The optimal amount of alkali was obtained for 5 % of sodium hydroxide.